Strengthening Digital Citizenship through Citizenship Education Based on Science, Technology and Society in Era 4.0 - Bali Widodo; Suwarma Al Muchtar; Endang Danial AR (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the strengthening of digital citizenship through science, technology and society-based Citizenship Education courses in the 4.0 era. The method used in this research is descriptive qualitative, collecting data through interviews, documentation and observation. The results of the study show that 1) strengthening digital citizenship through Civics Education courses based on science, technology and society in the 4.0 era is forming civic competence, 2) Strengthening digital citizenship through Citizenship Education courses requires digital habituation in students' daily lives. 3) Approach to Science, Technology and Society (STM) to answer the problems that exist in the community so that learning becomes more meaningful. Strengthening digital citizenship through science, technology and community-based civics learning in the 4.0 era in the end is towards smart and good citizens.